Protective effects of curcumin and vitamin E on carbon tetrachloride-induced nephrotoxicity in rats - Indira, Pala; Sivajyothi, P.; Sudhakara, G.; Venkatanarayana, G. (Technische Universität Dortmund, 2012)
The present investigation reports the protective effects of curcumin (CMN) and vitamin E against CCl4 induced oxidative stress and nephrotoxicity in rats. The toxicant CCl4 was used to induce nephrotoxicity at a dose of 1 ml/kg as 1:1(v/v) mixture with liquid paraffin twice weekly for 8 weeks. Plasma total protein, albumin, urea and creatinine concentrations were measured to assess the renal function. Antioxidant status in the kidney was estimated by determining the activities of glutathione peroxidase (GPx), glutathione reductase (GR), glutathione-S-transferase (GST), catalase (CAT) and superoxide dismutase (SOD) as well as by histopathological examination. CCl4 caused elevated levels of urea and creatinine while it decreased levels of total protein and albumin in plasma. Furthermore, CCl4 treated rats showed marked depletion of renal endogenous antioxidant enzymes. Oral administration of curcumin (100 mg/kg, daily for 8 weeks) and in combination with vitamin E (three times weekly for 8 weeks) showed significantly attenuated renal dysfunction by increased activity of antioxidant enzymes in kidney. It also increased the concentrations of plasma total protein and albumin, while reducing the concentration of urea and creatinine. Kidney sections of CCl4 induced rats showed deleterious alterations in micro anatomy. However, curcumin and vitamin E treatment prevented kidney damage induced by CCl4. This study reveals that curcumin in combination with vitamin E possesses strong antioxidant and kidney protective activity compared to curcumin alone.
EXCLI Journal ; Vol. 11, 2012
Keywords: carbon tetrachloride; curcumin; silymarin; vitamin E; 610